2012
DOI: 10.1007/s11999-012-2355-y
|View full text |Cite
|
Sign up to set email alerts
|

MRI is Unnecessary for Diagnosing Acute Achilles Tendon Ruptures: Clinical Diagnostic Criteria

Abstract: Background Achilles tendon ruptures are common in middle-aged athletes. Diagnosis is based on clinical examination or imaging. Although MRI is commonly used to document ruptures, there is no literature supporting its routine use and we wondered whether it was necessary. Questions/purposes We (1) determined the sensitivity of physical examination in diagnosing acute Achilles ruptures, (2) compared the sensitivity of physical examination with that of MRI, and (3) assessed care delays and impact attributable to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 20 publications
(69 reference statements)
1
54
0
4
Order By: Relevance
“…Ultrasound is a first-line examination in the event of Achilles tendon rupture, due to its ease of use, the ability to visualize the dynamic function of the tendon and finally its cost [8][9][10] . Other tests such as MRI and standard radiography can be used in the initial assessment of this pathology in addition to clinical diagnosis [11,12] . Several therapeutic methods are proposed for the treatment of an Achilles tendon rupture: conservative treatment by plaster immobilization, functional rehabilitation, classical surgical treatment and percutaneous or endoscopic suture [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is a first-line examination in the event of Achilles tendon rupture, due to its ease of use, the ability to visualize the dynamic function of the tendon and finally its cost [8][9][10] . Other tests such as MRI and standard radiography can be used in the initial assessment of this pathology in addition to clinical diagnosis [11,12] . Several therapeutic methods are proposed for the treatment of an Achilles tendon rupture: conservative treatment by plaster immobilization, functional rehabilitation, classical surgical treatment and percutaneous or endoscopic suture [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…It has proven more useful in the assessment of chronic ATR however, as timing is not so critical and the clinical diagnosis and even ultrasound appearances may not be conclusive. [13] The normal tendon shows low signal intensity on all MRI sequences, without focal defects. Chronic ruptures are seen as an area of low signal intensity on T1-weighted images and discontinued, altered signal on T2-weighted sagittal views.…”
Section: Investigationsmentioning
confidence: 93%
“…Magnetic resonance imaging (MRI) and ultrasound can aid in preoperative planning but are rarely necessary in making the diagnosis of acute Achilles ruptures [24]. Garras et al recently found there to be a 100 % sensitivity in diagnosing an acute rupture without MRI based on clinical findings alone [29].…”
Section: Presentation Physical Examination and Diagnosismentioning
confidence: 99%